Perancangan Interior Re-Desain Kaza Bowling Center di Surabaya - Steven Suprapto (Intra, 2017)
Nowadays, sports game center becoming more and more common in Surabaya because the demand for entertainment has increased rapidly from years to years. This can be seen with a lot of new game center that popping up across Surabaya recently. Kaza Bowling Center is one of the best game centers in Surabaya and the one and only bowling center in Surabaya. However, as the time pass by Kaza tend to lack facilities, and qualities compared to other new game centers nowadays. This matter caused because of there still no concept, and design style that can increase overall game center facilities and qualities. With a new solution, concept, and design style, Kaza might bring comfy yet fun environment, and become much more attractive for people to come. Therefore, with the solution, design style, and concept that has been made, Kaza might be the number one choice for people searching for entertainment.